An assessment of Sudan’s wheat value chains: Exploring key bottlenecks and challenges - Abdelaziz, Fatma; William, Amy; Abay, Kibrom A.; Siddig, Khalid (International Food Policy Research Institute, 2022)
Wheat is a strategic and political good in Sudan and has played a central role in the country’s economy during successive regimes. Disruptions in Sudan’s wheat value chain usually leads to shortages of wheat bread, price spikes, and political unrest. With the objective of ensuring sufficient grain supplies for domestic consumption, Sudan’s domestic and imported wheat sectors have been subject to several government interventions over the last decades. Most interventions have focused on and aimed to (i) stimulate domestic production, (ii) ensure a reliable flow of wheat imports to compensate for low domestic wheat production, and (iii) monitor wheat flour and bread distribution processes to limit leakage and wastage. Sudan has two distinct wheat value chains: one for imported wheat and one for domestic wheat. The imported wheat value chain involves three major actors: milling companies, wheat flour agents, and bakeries. The domestic (locally produced) wheat value chain involves four main actors: wheat producers, wheat grain wholesalers, wheat grain retailers, and consumers. To understand the landscape of the wheat sector in Sudan, this report relies on rapid assessment surveys of the main wheat value chain actors. The aim is to closely identify different value chain actors’ distinct roles of the and to explore their linkages. The report evaluates and identifies key bottlenecks that likely cause wheat and bread supply disruptions while also shedding light on untapped opportunities and possible policy options to improve the functioning of Sudan’s wheat sector. We document wheat value chain actors’ policy preferences, which vary depending on whether actors are engaged in the domestic or the imported value chain. The report highlights the differential impact of COVID-19 and related mobility restrictions on wheat value chain members. For example, while wheat production remains mostly unaffected by the outbreak of the COVID-19 pandemic, the marketing, trade, and distribution of wheat and wheat flour has been adversely affected by it.